Ignorance of 21 century, descending in valuable and behavior - ليلي تمن زامل (Al-Adab Journal, 2018)
The major understood that give general imaging about nature of community are behavior , modernity , civilization , inhumanity . And important major problems that undergo it the our community is scientific decline comparison with 20 century , as well as changing of originality behavior and appeared instead of behavior not controlled by religion and speech . According to the today generation busy with illusion , division and hatred because that living different contradiction and absence the rational thinking or romantic or combative or progressive thinking and all that because not obligation with religion . That lead to more suicide cases because the failure and foiling in structure of the person . The basic of all these problems is illiteracy which it reach about 50% in our Arabic country and spreading the poverty in our Arabic country that contain different wealth and strategic location but not uses in perfect benefit.